Giant tortoise genomes provide insights into longevity and age-related disease. Issue 1 (January 2019) - Quesada, Víctor; Freitas-Rodríguez, Sandra; Miller, Joshua; Pérez-Silva, José; Jiang, Zi-Feng; Tapia, Washington; Santiago-Fernández, Olaya; Campos-Iglesias, Diana; Kuderna, Lukas; Quinzin, Maud; Álvarez, Miguel; Carrero, Dido; et al.
Abstract Giant tortoises are among the longest-lived vertebrate animals and, as such, provide an excellent model to study traits like longevity and age-related diseases. However, genomic and molecular evolutionary information on giant tortoises is scarce. Here, we describe a global analysis of the genomes of Lonesome George—the iconic last member ofChelonoidis abingdonii —and the Aldabra giant tortoise (Aldabrachelys gigantea ). Comparison of these genomes with those of related species, using both unsupervised and supervised analyses, led us to detect lineage-specific variants affecting DNA repair genes, inflammatory mediators and genes related to cancer development. Our study also hints at specific evolutionary strategies linked to increased lifespan, and expands our understanding of the genomic determinants of ageing. These new genome sequences also provide important resources to help the efforts for restoration of giant tortoise populations. The genomes of two long-lived giant tortoises, including Lonesome George, reveal candidate genes and pathways associated with their development, gigantism and longevity.